Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer: [tex](x+3)^2+(y-6)^2 = 36\\\\[/tex]
==========================================================
Explanation:
If you apply the midpoint formula to the given points, you should find the midpoint is (3,6). This point represents the center of the circle. This means (h,k) = (3,6).
The radius is r = 6 because this is the distance from the center to either given endpoint. Either count out the spaces or use subtraction of the x coordinates. This works because the y coordinates are all the same.
Use those h, k and r values to plug them into the equation below
[tex](x-h)^2+(y-k)^2 = r^2\\\\(x-(-3))^2+(y-6)^2 = 6^2\\\\(x+3)^2+(y-6)^2 = 36\\\\[/tex]
which represents the equation of the circle we're after.
The graph is below.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.